Kearifan Lokal dan Strategi Komunikasi Public Relations di BUMN dan Perusahaan Swasta - Kriyantono, Rachmat; Sa’diyah, Halimatus (FISIP Universitas Atma Jaya Yogyakarta, 2018)
This study describes the connection between communication strategies of state-owned enterprises (BUMN) and private companies in Indonesia with its local culture. Contructivism was applied to explore qualitative data, involving the practitioners from BUMN and private companies. The research finds two propositions, i.e. the more local wisdoms are understood, the easier to create communication strategy of public relations that builds good relations with the public; communication strategy based on local wisdoms is used by both BUMN and private companies. The research contributes to enrich public relations study within Indonesian local perspectives.